2015
DOI: 10.15306/mvpjms/2015/v2i2/78295
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Efficacy of Topical Minoxidil 5% and Combination of Topical Minoxidil 5%, Topical Azelaic Acid 1.5% and Topical Tretinoin 0.01% on the Basis of Dermoscopic Analysis in Androgenetic Alopecia

Abstract: Background: Androgenetic alopecia (AGA) more commonly known as male pattern baldness affects up to 50% of men worldwide. Tretinoin prolongs anagen phase and increases percutaneous absorption of minoxidil three fold. Azelaic acid is an inhibitor of 5 alpha reductase and could be an effective agent in the treatment of androgen related pathology of human skin. Aims and Objective: 1) To study the efficacy of topical minoxidil 5% in treatment of androgenetic alopecia. 2) To study the efficacy of combination of topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A valuable insight into the patient diagnosis and treatment could be attained when the results of these techniques are interpreted with a comprehensive clinical picture. More recent studies reported that the use of dermoscopy of scalp and hair in the clinical assessment of hair disorders could provide a higher diagnostic capability than simple clinical examination [ 91 , 92 , 93 ]. Figure 11 and Figure 12 illustrate the clinical photographs and the dermoscopic pictures of group A and group B, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A valuable insight into the patient diagnosis and treatment could be attained when the results of these techniques are interpreted with a comprehensive clinical picture. More recent studies reported that the use of dermoscopy of scalp and hair in the clinical assessment of hair disorders could provide a higher diagnostic capability than simple clinical examination [ 91 , 92 , 93 ]. Figure 11 and Figure 12 illustrate the clinical photographs and the dermoscopic pictures of group A and group B, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 Topical minoxidil is commonly used in the treatment of AGA; it prolongs the anagen growth phase and gradually develops miniaturized follicles (vellus hairs) into mature terminal hairs. 2 In the last few years, the use of lasers in treating hair loss has well developed through many means. The paradoxical hair growth noticed after laser hair removal is a clinical example of photo-induced hair growth.…”
Section: Discussionmentioning
confidence: 99%
“…The continuation of the treatment is required to keep the profit. 2 Recently, laser treatment for hair loss has become very popular; it has also been promoted as a preventative measure against AGA as there is evidence that laser light stimulates hair growth at some wavelengths. 3 Laser-assisted drug delivery (LAD) is an evolving technology with potentially broad clinical applications.…”
Section: Introductionmentioning
confidence: 99%